Models of Student Engagement in Music Education Classroom in Higher Education - Wang, Aiqin (Frontiers in Psychology, 2021)
Higher education is undergoing a paradigm move from passive learning towards active learning. Student engagement is assumed to be a significant criterion and gauge for the quality of the student skill for higher education; however, in the literature, the term engagement remains to be vague to delineate, and it is construed in different ways. Since institutions accentuate preparing alumnae for life further than their education, student engagement has turned out to be a priority for music education, and within the last five years, the attention was drawn to ‘Students as Partners’ (Healey & Healey, 2018) as a response to ‘students as consumers’ construct manipulating higher education theory (Matthews, 2017). Concerning the literature review, the meaning of student engagement, determinants influencing it, and its merits are brought together. In conclusion, the implications of student engagement are presented, and new guidelines for future research are depicted.